Tetrameric PilZ protein stabilizes stator ring in complex flagellar motor and is required for motility in Campylobacter jejuni - Yuanyuan Chen; Shoichi Tachiyama; Yuqian Li; Xueyin Feng; Hang Zhao; Yanmin Wu; Yu Guo; María Lara-Tejero; Canfeng Hua; Jun Liu; Beile Gao (Proceedings of the National Academy of Sciences, 2025)
Rotation of the bacterial flagellum, the first identified biological rotary machine, is driven by its stator units. Knowledge gained about the function of stator units has increasingly led to studies of rotary complexes in different cellular pathways. Here, we report that a tetrameric PilZ family protein, FlgX, is a structural component underneath the stator units in the flagellar motor of Campylobacter jejuni . FlgX forms a stable tetramer that does not bind cyclic di-GMP (c-di-GMP), unlike other canonical PilZ domain–containing proteins. Cryoelectron tomography and subtomogram averaging of flagellar motors in situ provide evidence that FlgX interacts with each stator unit and plays a critical role in stator ring assembly and stability. Furthermore, FlgX is conserved and was most likely present in the common ancestor of the phylum Campylobacterota . Overall, FlgX represents a divergence in function for PilZ superfamily proteins as well as a player in the key stator–rotor interaction of complex flagellar motors.